Confirmation of Factors Affecting Self-Care Activities of Patients with Hypertension - Istiani, Hari Ghanesia; Rokhmiati, Eka (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2021)
Introduction: Hypertension is one of the non- communicable diseases that causes the highest mortality. Self-care activities are factors that determine the health status and quality of life of people with hypertension. Objectives: The aim of the study was to determine the direct and indirect effects and the magnitude of the variables of the role of health workers, family functions, health literacy, and self-efficacy on self-care activities for hypertension sufferers at the Tanah Sareal Health Center, Bogor City in 2018. Methods: The method used in the study this is a quantitative approach that uses adesign cross-setional. The sample used was 80 hypertension patients. The analysis used is the Structural Equation Model (SEM) using SmartPLS 2.0. Results: The results of hypothesis testing with smartPLS resulted in research findings, namely that the self-care activities of hypertension sufferers were influenced by the role of health workers (16.98%), family function factors (12.32%),factors health literacy (26.66%), and self-efficacy factor (25.27%). The total amount of direct influence on self-care activities of hypertension sufferers is 81.23% and the indirect effect is 1.53%. The analysis result model can explain 99.1% of the diversity of data and is able to study the phenomena used in the study, while 0.9% is explained by other components that are not present in this study. Conclusion: There is a direct influence between the role of health workers, family function, health literacy and self-efficacy on the self-care activities of hypertension sufferers at Tanah Sareal Health Center.